PERBEDAAN MOTIVASI IBU DALAM PEMILIHAN KONTRASEPSI IMPLAN SEBELUM DAN SESUDAH PROMOSI KESEHATAN MEDIA VIDEO DI DESA REMBANGKEPUH KECAMATAN NGADILUWIH KABUPATEN KEDIRI - Yunarsih Yunarsih; Sumi Dwi Antono; Retna Lea Santika (Akademi Keperawatan Dharma Husada Kediri, 2018)
The implant contraceptive method is one of the contraceptive methods that are less attractive to the public, especially couples of childbearing age, although the effectiveness of implant contraception is very high. The area in Kediri District which have the lowest implant acceptor is in he village of Rembangkepuh the working area of the Wonorejo Health Center. Lack of motivation for couples of childbearing age to participate in family planning is caused by several things, one of them is because socialization is still not implemented optimally. The purpose of this study was to determine differences in maternal motivation in the selection of implant contraception before and after the health promotion of video media. This study uses a one-group pretest-posttest design and used simple random sampling technique with 30 subjects. The results showed that the mother's motivation in choosing the implant contraception before being given the highest video media health promotion was in the highly unmotivated category as many as 19 respondents (63%), while the mother's motivation in choosing implant contraception after being given health media promotion was in the highly motivated category of 15 respondents ( 50%). Statistical tests were performed using Wilcoxon Match Paired Test statistic obtained Z count> Z table that is 4,294> 1,645 so it can be concluded that there are differences in maternal motivation in the selection of implant contraception before and after vidio health promotion.. Keywords: Health Promotion, Implants, Motivation